Analysis Of The Influence Of Job Satisfaction And Organizational Commitment On Turnover Intention In PT. Hadji Kalla Toyota Palopo Branch - Fitrahayu Fitrahayu; Muh. Idrus Taba; Haeriah Hakim (STIE AMKOP, 2023)
The ultimate goal of this research is to analyze the effect of job satisfaction and organizational commitment on turnover intention partially. 68 employees were sampled in this study. Quantitative research, with collection techniques using survey methods by distributing questionnaires that have been tested using validity and reliability tests and data analysis using multiple regression. This observation results in job satisfaction at PT Hadji Kalla Toyota Palopo Branch having an (-) and significant effect on turnover intention, so that organizational commitment has an effect on (+) but not too strong on turnover intention. Then job satisfaction and organizational commitment together have a significant influence on turnover intention. Keywords: Job Satisfaction, Organizational Commitment, and Turnover Intention